Calcium-induced skim milk gels with addition of caseinglycomacropeptide: A multipurpose matrix for the formulation of semisolid dairy products - Acosta, Nadia Belen; Mengatto, Luciano Nicolás; Manzo, Ricardo Martín; Costabel, Luciana Maria; Olivares, María Laura (Wiley, 2025)
Background: Calcium-induced milk gels are excellent matrices for formulating calcium-fortified semisolid foods. The optimisation of these gels to enhance their technological and bioactive properties is of interest to both academia and industry. Aim: This study examines the gelation process and physicochemical properties of calcium-induced skim milk gels with caseinglycomacropeptide. Methods: Skim milk concentrates were prepared with skim milk powder (30% w/w), calcium lactate (90 mmol/kg) and caseinglycomacropeptide (1.5 and 3% w/v). Gels were prepared by heating at 80°C for 15 min and analysed after 1 day and after 20 days of storage at 4°C. Rheological properties, Fourier transform infrared spectroscopy, syneresis, water holding capacity, protein hydration and calcium retention in the gel matrix were evaluated. Caseinglycomacropeptide concentration and storage time were the main statistical factors. Major Findings: Time sweep tests showed rapid gel formation with similar behaviour across samples. Gels exhibited a homogeneous structure, no phase separation and pseudoplastic behaviour. Frequency sweeps indicated that fresh gels had similar viscoelastic properties, with moduli dependent on frequency. The addition of caseinglycomacropeptide slightly increased elasticity. After storage, G′ and G″ values increased, and frequency dependence decreased, suggesting structural evolution and stronger interactions, enhancing gel firmness. Fourier transform infrared spectroscopy suggested that calcium binding to proteins and caseinglycomacropeptide induced conformational changes. Heat treatment effects were evidenced by decreased intensities in amide I, II and III regions, indicating protein denaturation. No syneresis was observed. Water holding capacity and protein hydration remained unchanged. However, calcium retention increased with higher caseinglycomacropeptide levels, suggesting it binds calcium within the matrix. Industrial Implications: This methodology is suitable for industrial applications, enabling the development of calcium-fortified products, such as desserts, dressings and spreads.